2017
DOI: 10.1149/2.1441712jes
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Vinylene Carbonate (VC) as Additive in Graphite/LiNi0.5Mn1.5O4Cells

Abstract: Vinylene Carbonate (VC) is an effective electrolyte additive to produce a stable solid electrolyte interphase (SEI) on graphite anodes, increasing the capacity retention of lithium-ion cells. However, in combination with LiNi 0.5 Mn 1.5 O 4 (LNMO) cathodes, VC drastically decreases cell performance. In this study we use on-line electrochemical mass spectrometry (OEMS) and electrochemical impedance spectroscopy (EIS) with a micro-reference electrode to understand the oxidative (in-)stability of VC and its effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
126
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 96 publications
(135 citation statements)
references
References 41 publications
9
126
0
Order By: Relevance
“…All Nyquist plots show two distinct semi-circles, one at high frequencies that shows the same resistance for all the materials both at cycle 2 and 50 (increasing from ≈8 to ≈20 ), and one at lower frequencies which differs significantly for the different compositions. Previous studies have shown that the semi-circle at high frequencies for cathode electrodes can be assigned to a contact resistance at the interface of the cathode electrode with the aluminum current collector, 50,51 which can also be rationalized by considering the electrode capacitance corresponding to this first semi-circle:…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…All Nyquist plots show two distinct semi-circles, one at high frequencies that shows the same resistance for all the materials both at cycle 2 and 50 (increasing from ≈8 to ≈20 ), and one at lower frequencies which differs significantly for the different compositions. Previous studies have shown that the semi-circle at high frequencies for cathode electrodes can be assigned to a contact resistance at the interface of the cathode electrode with the aluminum current collector, 50,51 which can also be rationalized by considering the electrode capacitance corresponding to this first semi-circle:…”
Section: Resultsmentioning
confidence: 97%
“…Detailed studies onto the origin of those contact resistances are reported elsewhere. 50,51 The second semi-circle at lower frequencies can then be assigned to a charge-transfer resistance (R CT ), which clearly differs largely for the different HE-NCM materials. First examining their impedance directly after the two activation cycles (Figure 6a), it can be seen that R CT decreases with increasing Li 2 MnO 3 content and thus with increasing oxygen release ( Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…This is largely related to the fact that in commercialscale cells, the ratio of active materials to electrolyte solution and void volume is typically ∼10 times higher compared to the lab-scale cells used here. 37,56 Strehle et al 16 recently showed that under these conditions, the majority of CO 2 released from VC reduction would remain dissolved in the electrolyte solution instead of being released into the gas headspace of the cell. This is illustrated by first estimating the amount of dissolved CO 2 by Henry's law 2: where n CO2(el) is the amount of CO 2 dissolved in the liquid electrolyte solution, V el is the volume of the electrolyte solution, c el is the total molar concentration of the electrolyte solution (i.e., solvent and salt) and K H is the Henry constant of CO 2 in the electrolyte solution in units of pressure.…”
Section: Discussionmentioning
confidence: 99%
“…This increase of the LNMO cathode's contact resistance fits very well to the observation that a delamination of the LNMO electrode from the current collector occurs during cycling at elevated temperatures (60 • C), 31 the underlying mechanism of which will be a subject of a future work. 32 Compared to the contact resistance, the pore resistance (R Pore , green symbols) increases from an initial value of ≈3.5 to ≈5 after 85 cycles, while the charge transfer resistance at 4.4 V FC (R CT-non-blocking , purple symbols) starts at ≈0.5 and increases to only ≈0.7 after 85 cycles. Thus, the contact resistance shows the strongest increase over the 85 charge/discharge cycles of +300%, while the pore and charge transfer resistance at 4.4 V only increase by ≈45% and ≈30%, respectively (see Figure 9b).…”
Section: Lnmo Cathode Impedance Evolution In Lnmo/graphite Cells-mentioning
confidence: 99%